Merdeka Curriculum Innovation: Grand Design for Digital Literacy Learning in Special School - Wahyuni, Sri; Darmayunata, Yuvi; Zudeta, Effran; Sajid, Muhammad Dani Fauzan; Syahdan, Syahdan (Educative: Jurnal Ilmiah Pendidikan, 2023)
Creative and inspiring rules are competencies in independent learning. The Merdeka curriculum needs to integrate digital literacy into learning. digital literacy is important especially for students who attend the special school in order to have the ability to understand and implement digital literacy-based learning processes. To develop digital literacy in SLB, a digital literacy learning design is needed. In Riau Province, there is no special school education unit that has a digital literacy-based curriculum, based on interviews with supervisors and the head of the Riau special school principals association. Based on this description, the research team felt it was important to develop digital literacy-based learning in SLB. The aim to be achieved through this research is the preparation of a learning design that can be implemented in special school education units. The research methodology used is a research and development with  research stages: exploratory study, FGD exploratory study, drafting of the model, conceptual and operational testing of the model, and developing a digital literacy-based curriculum. The results of the study are in the form of a learning design that includes a digital literacy learning framework and a learning development formula for the digital literacy curriculum. It can be concluded that there is a significant difference in teacher knowledge between before and after following the digital literacy-based curriculum model of 0.892 (89.2%) at α = 0.05.